TOMOGRAPHIC RELATIONSHIPS BETWEEN RETINAL NEOVASCULARIZATION AND THE POSTERIOR VITREOUS IN PROLIFERATIVE DIABETIC RETINOPATHY. Issue 7 (July 2017) - Vaz-Pereira, Sara; Dansingani, Kunal K.; Chen, Kevin C.; Cooney, Michael J.; Klancnik, James M.; Engelbert, Michael
Abstract : Purpose: To describe anatomical relationships of retinal neovascular complexes (NVCs) and the posterior vitreous in proliferative diabetic retinopathy using spectral domain optical coherence tomography. Methods: Cross-sectional study. Neovascular complexes were imaged using spectral domain optical coherence tomography in 51 eyes of 37 patients. The relationship of NVCs to the posterior vitreous cortex and posterior vitreous spaces, such as the premacular bursa, prevascular vitreous fissures, and perimacular cisterns, was analyzed. Results: In the 77 NVCs evaluated, 61 (79%) had grown along the outer surface of the posterior hyaloid face, and vitreoschisis was present in 37 (48%). The "wolf's jaw" configuration was present in 9% and resulted from NVC arising from the arcades and proliferating along the posterior hyaloid face. By contrast, NVCs that invaded the bursa originated from smaller venous tributaries more distant from the arcades. The premacular bursa and prevascular vitreous fissure/perimacular cistern were invaded infrequently, respectively, in 15% and 38% ( P = 0.137). Conclusion: Tomographic analysis of diabetic NVCs showed that most NVCs arise and grow along the posterior hyaloid face and that vitreoschisis is more prevalent than what has been found in ultrasound studies. The wolf's jaw configuration does not seem to result from the invasion of the bursa, as previously suggested. Abstract : Analysis of the relationship of retinal neovascular complexes and the posterior vitreous in proliferative diabetic retinopathy suggests that the posterior hyaloid face, prevascular vitreous fissures, and perimacular cisterns commonly serve as scaffolds for neovascularization. Vitreoschisis is present in half of cases, and "wolf's jaw" configuration results from neovascular growth along the arcades rather than the invasion of the bursa premacularis.